Influence of the movement deviation on metabolic economy of the V1 and V2 cross-country skate techniques - Moore, S. R.; Weich, C.; Torchia, I.; Jensen, R. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
The purpose of the current study was threefold; (i) to determine if significant differences exist in economy and movement variability between the V1- and V2-skate techniques in elite cross-country skiers; (ii) to determine the effects on economy and movement incurred by a V1 and V2 technique-specific training period; (iii) to determine if a relationship exists between the economic cost and variability of movement of the V1 and V2 techniques.